Drum roll, please - Bigelow, Lisa Jenn (Harper, an imprint of HarperCollins Publishers, 2018)
Melly only joined the school band because her best friend, Olivia, begged her to. But to her surprise, quiet Melly loves playing the drums. It<U+2019>s the only time she doesn<U+2019>t feel like a mouse. Now she and Olivia are about to spend the next two weeks at Camp Rockaway, jamming under the stars in the Michigan woods. But this summer brings a lot of big changes for Melly: her parents split up, her best friend ditches her, and Melly finds herself unexpectedly falling for another girl at camp. To top it all off, Melly<U+2019>s not sure she has what it takes to be a real rock n<U+2019> roll drummer. Will she be able to make music from all the noise in her heart?